Predictors of polytrauma outcome in children on the first day of treatment in ICU - K. V. Pshenisnov; Yu. S. Aleksandrovich; A. S. Lipin; G. P. Tihova; P. I. Mironov; S. A. Blinov; V. A. Evgrafov; V. E. Ironosov; V. A. Kaziakhmedov; A. N. Kondin; O. V. Kuzmin; I. N. Popova; et al. (Вестник анестезиологии и реаниматологии, 2024)
The objective was to identify predictors of polytrauma outcome in children on the first day of treatment in ICU.Materials and methods. Design – multicenter, cohort, retrospective, observational study. 225 children with polytrauma were examined. The average age of children was 10 (4–14) years. There were 148 (65.8%) boys. In 65.2% of cases, the injury was received as a result of a traffic accident, catatrauma occurred in 32.6% of polytrauma. The AIS score was 34 (25–48) and the PTS score was 5 (2.0–8.0). The duration of artificial lung ventilation was 12 (0–97) hours, and treatment in ICU – 5 (2–8) days. Death was in 14.2% of cases. Results. An increase in Glasgow Coma Scale (GCS) and SpO2 by one unit (1 point, 1%) was found to reduce the risk of adverse outcome by 44% and 9%, respectively, and an increase in creatinine concentration and international normalized ratio by one unit increased the probability of patient death by 4.3 and 15.8 times, respectively. A mathematical formula was developed to assess the risk of an unfavorable outcome of polytrauma in children at the time of admission to the ICU: OR = exp (3.74–0.58 · [GCS score] – 0.09 · [SpO2] + 0.06 · [Creatinine] + 2.62 · [INR]. Its accuracy is 96.4%; sensitivity 83.4%; specificity 98.7%.Conclusion. Predictors of unfavorable outcome of polytrauma in children at admission to ICU are low scores on the Glasgow Coma Scale, severe hypoxemia, coagulopathy and kidney damage.